Turning the King Tide: Understanding Dialogue and Principal Drivers in an Online Co-Created Investigation. (13th February 2019) - Peterman, Karen; Bevc, Christine; Kermish-Allen, Ruth
Online learning communities for citizen science have been growing in number and scale in recent years. The WeatherBlur project was designed to apply knowledge-building theory to a non-hierarchical online citizen science community for students in grades three to eight, their teachers, and scientists. This case study explores one investigation to determine the kinds of interactions that encouraged online knowledge-building and the individuals who served as the key drivers for the investigation. Posts from the project's discussion board were analyzed via a discourse analysis. The results indicated that students, teachers, and scientists initiated online discourse at similar rates, affirming the project's non-hierarchical design. Two knowledge-building constructs were used to initiate dialogue, including comments that added to the quantity and then quality of information in the conversation and those that included some conceptual advancement. Photos were also used more often to initiate rather than respond to conversation. By comparison, ongoing conversation was sustained by comments that enhanced the quality of information shared. Using activity log data, the results from a social network analysis indicated high variation in posting frequency, high probability of reciprocity, and dense core-periphery structure. Both the discourse analysis and social network analysis revealed multiple ways for individuals to become core to the network and thus primary drivers for the investigation. The findings are discussed in relation to knowledge-building in online citizen science communities.